Pijat oksitosin dan Frekuensi Menyusui berhubungan dengan Waktu Pengeluaran Kolostrum pada Ibu Post Sectio Caesarea di RS Kota Bandung - Dian Nur Hadianti; Rika Resmana (Alma Ata University Press, 2016)
Colostrum is the first breast milk that comes out which contains many substances anti-infectionfor the newborns,so when a newbornwere not given the colostrum will be susceptible to infectious diseases. According Riskesdas 2013, newborn babies who received breast milk (colostrum) during 24-47 hours by 13%. The results of a survey of 9 from 15 Post SC who give colostrum to their babies in 24 hours. The purpose of this study was to know The Relationship Between Massage Oxytocin and Breastfeeding Frequencies With The Excretion Time of Colostrum in the Post Partum Caesarean. The factors are oxytocin massages, breastfeeding frequencies, breast caress, the nutritional status of the pregnant and parites.The study methods used Case-Control Study. The sample was selected by quota sampling of 60 respondents, consisting of 30 cases of the post SC who colostrum out after 24 hours and 30 controls the post SC who colostrum out less than 24 hours. The study used primary data with observational techniques to post Sectio Caesaria (SC) who were treated at the Hospital. The bivariant data were analyzed by Chi-Square test. The results showed that p-value 0.001 (p<0.05), with OR 7.00 (95% CI 3.1-15.8) means the post SC mothers which, given oxytocin massage was 7.0 times more likely excretes colostrum on the first day after the delivery. And the OR 15.5 (95% CI 3.8-63.4) means the colostrum that execretes on the first day after delivery was 15.5 higher in a post SC mother which breastfeed 7 times a day. Conclusion, there was a significant relationship between oxytocin massage with excretion time and there was a significant relationship between the frequency of breastfeeding with a excretion time of colostrum in the post SC.